Design and analysis of an ultra‐thin crystalline silicon heterostructure solar cell featuring SiGe absorber layer. Issue 4 (7th March 2018) - Hussain, Shahzad; Mehmood, Haris; Khizar, Muhammad; Turan, Rasit
Abstract : Here, the authors studied a silicon–germanium (Si1− x Ge x ) absorber layer for the design and simulation of an ultra‐thin crystalline silicon solar cell using Silvaco technology computer‐aided design. Seeking ways to design and fabricate solar cells using 100 μm thicker silicon substrates is the subject of intense research efforts among the photovoltaic (PV) community. The aim is to further reduce the substrate thickness to 20 μm without compromising the efficiency of the solar cell. A thin layer of SiGe film with the Ge composition of 15% has been introduced in this work that assists in absorbing the longer wavelength of the sunlight spectrum. The effects of the doping concentration and absorber layer thickness on the conversion efficiency have been examined. The simulated results exhibited significant enhancement in the sunlight absorption as compared to the reference structure based on crystalline silicon. The highest efficiency of 16.8% with an overall solar cell thickness of ∼26 μm has been observed. The proposed heterostructure solar cell design will support the industrial development of an efficient, low‐cost, shorter energy payback time, and light‐weight PV technology for its widespread implementation.